THE IMPORTANCE OF PEDAGOGICAL COMPETENCE ON DEVELOPING LECTURERS’ PROFESSIONAL CAREER: AN EVALUATIVE RESEARCH - Nurul Hasanah; Iffah Budiningsih; Qurrota A’yun; Muhammad Fahrudin (Akademika, 2023)
TPACK stands for technological pedagogical content knowledge is a learning paradigm which integrates technical knowledge into content and pedagogical ideas. With education trends in the digital age heavily reliant on the incorporation of technology in the teaching and learning process, TPACK model has become a necessity for lecturers. The purpose of this study is to assess the pedagogical proficiency of UIA instructors and to offer suggestions for improvement. This study design is for a survey. The whole student body of UIA Jakarta is the target demographic. While the undergraduate students in the sixth semester make up the small population. Simple random sampling was utilized as the sample strategy. Data are collected via questionnaire, and descriptive statistics are used for analysis. The results showed that the average score of lecturers' pedagogical competency was 3.51 (excellent), and that greeting and prayer at the start and conclusion of the course received the highest score of 3.63. In order to close the accomplishment gap in learning, pedagogical proficiency is crucial. The study's implications include urging UIA lecturers to take part in Instructional Techniques Training (PEKERTI) for professional certification, incorporating the TPACK model into their instruction, and making sure that there is sufficient access to and high-quality ICT resources to support academic activities on campus.